Evaluation of BOSEH (Bike on the Street Everybody Happy) Program in Bandung City - Aria Mahendra Chandra; Mudiyati Rahmatunnisa; Slamet Usman Ismanto (Journal of Community Service and Empowerment, 2025)
The bike sharing program in Bandung City known as "BOSEH" (Bike on The Street Everybody Happy) was adopted as a strategic step to address the increasingly complex urban transportation issues. After running for a period of six years, BOSEH has encountered several challenges that need attention, such as a decrease in registration numbers, a decline in the number of active shelters, and poor shelter conditions. These issues have the potential to hinder accessibility and comfort for BOSEH users, indicating the need for improvements in the management and maintenance of these shelters to function optimally. Based on evidence gathered through observation and document review, this research will evaluate the BOSEH program in Bandung comprehensively. The aim of this research is to identify the achievements of BOSEH, which will be evaluated using the Context, Input, Process, and Product (CIPP) framework by Stufflebeam. This study applies a qualitative method with a case study approach to obtain rich and in-depth data through information collection from various sources, such as direct observation, interviews with stakeholders, and document analysis related to the BOSEH program. The results of this research show that the BOSEH program has been aligned with the identified needs in BUMP but faces challenges in implementation. To improve the effectiveness of the program, improvements in thorough planning, transparent budget allocation, infrastructure enhancement, and human resource quality are necessary, as well as improving shelter management, customer service, and promotional activities. Thus, BOSEH can have a more significant impact in creating the desired cycling culture and enhancing urban mobility in Bandung